DETAIL ENGINEERING DESAIN (DED) SISTEM PENYALURAN AIR LIMBAH DAN INSTALASI PENGOLAHAN AIR LIMBAH KAWASAN INDUSTRI BSB CITY, MIJEN KOTA SEMARANG - Fazalaili Rahmawati A; Wiharyanto Oktiawan; Winardi Dwi Nugraha (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
ABSTRACT BSB City Industrial Estate is an industrial area which activities and centrally located in the district Mijen Semarang city, industrial area contains manufacturing and warehousing industries. this area will be constructed wastewater distribution system planning and Wastewater Treatment Plants. Widely held at the industrial park with an area of ± 110 ha area for existing or for future development. The distance between one industry to another with regular road network large enough to transport passing, the contours of which are in the industrial area has a contour in the form of hills and down into the river, this allows gravity flow drainage system. Distribution system which was selected to be applied in the industrial BSB City is a conventional system, since BSB City industrial area has a large area of land with a greater load distribution, so that the required pipe diameter is relatively large with no dependence on the availability of clean water. In addressing pollution would happen then to system off site, which means that the distribution of industrial waste water through a closed pipeline (sewerage system). Furthermore, for industrial wastewater treatment plant used wells equipped with pumps collector, barscreen, equalization basin, primary clarifier, activated sludge basin, and sludge drying bed. It hopefully will be able to overcome the environmental problems in the industrial area BSB City, Mijen Semarang City. In addition, off-site system and its wastewater treatment plant is expected to create the industry's healthy and environmentally friendly